NKVD kariuomenės dokumentai Rusijos karo archyve - Anušauskas, Arvydas (Genocidas ir rezistencija, 1997)
Historians studying the armed struggle against the Soviet invaders in 1944–1953 are constantly confronted with the problem of identifying the military structures of occupation. The NKVD army regiments, which were tasked with the military suppression of the armed resistance, were sometimes stationed in Lithuania, Latvia, Estonia, western Ukraine or western Gudiya (Belarus) for very short periods. They were continuously changing their locations as they followed the frontlines or were relocated for punitive military operations to new territories. It is therefore very important to review and assess the whole system of military suppression in the Soviet Union, not just part of it. The archival sources available in Lithuania made it possible to identify or trace some of the NKVD–MGB troops that were active during the period in question, while the documents of the NKVD–MGB troops were carefully preserved in the Russian State Military Archive. This year, the author of this article was able to consult the files in the Russian State Military Archive.